The Year of the Four Emperors and the Revelation of John: The `pro-Neronian' Emperors Otho and Vitellius, and the Images and Colossus of Nero in Rome - van Kooten, George H. (2007)
This article draws attention to the events of the `Year of the Four Emperors', the period of unrest and civil war which followed Nero's death in 68 CE. Their bearing on the Revelation of John has been underestimated. My aims are to demonstrate the centrality of Nero in John's understanding of the seven-headed beast, and its image, and to propose a precise dating for the composition of Revelation in the period under Galba, Otho and Vitellius in 68/69 CE. This involves an analysis of Nero's Golden House, his colossal statue and the pro-Neronian attitude of his successors Otho and Vitellius. After my consistent rereading of Revelation in the context of 68/69 CE, I set out to disprove the common interpretation of Revelation, which draws upon the provincial imperial cult in Asia under Domitian. I finish by showing the relevance of Nero's expected return for a reading public in the Roman province of Asia.
Keywords: Year of the Four Emperors; Colossus of Nero; Golden House; Revelation of John; Otho and Vitellius; Nero